From MDD concepts to experiments and illustrations - Babau, Jean-Philippe; Champeau, Joël; Gérard, Sébastien (ISTE, 2006)
This book includes contributions from academic and professional experts on a range of topics related to MDD practices, methods and emerging technologies. After introducing general concepts about modeling and how to implement model transformations, two presentations provide an overview of the Marte profile. Coverage is then given to the most common aspects of MDD for DRES: structuring architectures using components, designing hardware architecture, evaluation and validation through tests and performance analysis. Finally, guidance is given as to how and why MDD should be used by presenting a to.